Characterization of WO3 Thin Films Grown on Silicon by HFMOD - Joel Díaz-Reyes; Roberto Castillo-Ojeda; Miguel Galván-Arellano; Orlando Zaca-Moran (Advances in Condensed Matter Physics)
We studied the effect of annealing temperature on the physical properties of WO3 thin films using different experimental techniques. WO3 has been prepared by hot-filament metal oxide deposition (HFMOD). The films, chemical stoichiometry was determined by X-ray photoelectron spectroscopy (XPS). The monoclinic single-phase nature of the as-deposited films, structure was changed to triclinic structure by annealing them at higher temperatures than 400°C, which has been determined by the X-ray diffraction analysis. By Raman scattering is confirmed the change of crystalline phase, of monoclinic to triclinic, since that lattice vibrational modes of as-deposited WO3 and annealed at 500°C present clearly differences. WO3 band gap energy can be varied from 2.92 to 3.15 eV by annealing WO3 from 0 to 500°C as was obtained by transmittance measurements. The photoluminescence response of the as-deposited film presents three radiative transitions observed at 2.85, 2.41, and 2.04 eV that could be associated with oxygen vacancies; the first one is shifted to higher energies as the annealing temperature is increased due to the change of crystalline phase of the WO3.